2019
DOI: 10.1007/s11590-019-01456-3
|View full text |Cite
|
Sign up to set email alerts
|

Mixed uncertainty sets for robust combinatorial optimization

Abstract: In robust optimization, the uncertainty set is used to model all possible outcomes of uncertain parameters. In the classic setting, one assumes that this set is provided by the decision maker based on the data available to her. Only recently it has been recognized that the process of building useful uncertainty sets is in itself a challenging task that requires mathematical support.In this paper, we propose an approach to go beyond the classic setting, by assuming multiple uncertainty sets to be prepared, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Different uncertainty sets and their geometric relationship are studied in [LDF11]. Recently mixed uncertainty sets, combining most of the popular uncertainty classes into one set, were studied in [DGR20]. Next to the classical robust optimization approach, several less conservative approaches have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Different uncertainty sets and their geometric relationship are studied in [LDF11]. Recently mixed uncertainty sets, combining most of the popular uncertainty classes into one set, were studied in [DGR20]. Next to the classical robust optimization approach, several less conservative approaches have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…where F ∈F min k∈F f (x x x,c c c k ) F ∈F max k∈F f (x x x,c c c k ) ∈ [0, 1]. Observe that ( 13) is a special case of the mixed-uncertainty robust optimization problem discussed in [9], where uncertainty sets are given and we would like to solve min…”
Section: Approximation Algorithms For the Robf Problemmentioning
confidence: 99%
“…In [9] it has been shown that solving the nominal problem min x x x∈X f (x x x, ĉ c c) with the cost verctor ĉ c c = F ∈F m(F ) 1…”
Section: Approximation Algorithms For the Robf Problemmentioning
confidence: 99%
“…In the following, we may also write c i = c i + d i to denote the upper bound on the costs of item i in interval or budgeted uncertainty sets. Many more uncertainty sets have been considered, including ellipsoidal uncertainty sets [BTN98,CG17], data-driven polyhedral sets based on statistical testing [BGK18] or machine learning [SHY17], or even combinations of multiple sets simultaneously [BSS19,DGR20].…”
Section: Problem Definitionsmentioning
confidence: 99%